The Acute Influence of Running-Induced Fatigue on the Performance and Biomechanics of a Countermovement Jump - Peimin Yu; Zhen Gong; Yao Meng; Julien S Baker; Bíró István; Yaodong Gu (Applied Sciences, 2020)
Lower limb kinematics and kinetics during the landing phase of jumping might change because of localized muscle fatigue. This study aimed to investigate the acute influence of running-induced fatigue on the performance and lower limb kinematics and kinetics of a countermovement jump. A running-induced fatigue protocol was applied to fifteen male subjects. Participants were asked to perform three successful countermovement jumps before and after fatigue. Kinematic and kinetic data were collected to compare any fatigue influences. Wilcoxon signed-rank tests and paired-sample t-tests were used to analyze the data. Running-induced fatigue did not significantly change vertical jump height and peak vertical ground reaction forces (GRF) during the push-off and landing phases. Lower limb biomechanics significantly changed, especially kinematic parameters. During the push-off phase, fatigue resulted in an increased ankle peak inversion angle, knee minimal flexion angle, knee peak abduction angle, and hip peak flexion moment. In addition, the range of motion (ROM) of the ankle and knee joints in the frontal plane was also increased. Certain parameters decreased as a result of fatigue, such as the ankle peak internal rotation angle, hip peak abduction angle, the ROM of the ankle joint in the sagittal plane, and ROM of the hip joint in the frontal plane. During the landing phase, the peak inversion angle and peak external rotation angle of the ankle joint, peak abduction angle of the knee and hip joint, ROM of the ankle joint in the horizontal plane, ROM of the ankle and knee joint in the frontal plane were all increased as a result of fatigue. The knee peak flexion moment and hip peak extension moment, however, were decreased. Under fatigue conditions, lower limb kinetics and kinematics were changed during both the push-off and landing phases. More attention should be focused on the landing phase and the last period of the push-off phase due to potentially higher risks of injury. The findings of the current study may be beneficial to athletes and coaches in preventing jumping related injuries.